Intracranial Pressure Monitoring Location: A Pilot Study on the Validation of Subdural Site with the Intraventricular Site - Bharadwaj, Suparna; Sundaram, Mouleeswaran; Chakrabarti, Dhritiman; Muthuchellappan, Radhakrishnan (Asian Journal of Neurosurgery, 2024)
Introduction Knowledge of preoperative and intraoperative intracranial pressure (ICP) enables the neuroanesthesiologist to optimize cerebral perfusion pressure. However, ICP is rarely monitored during the intraoperative period. In this report, subdural site ICP measurement is validated with intraventricular ICP measurement, and the feasibility of subdural ICP monitoring during the intraoperative period is discussed.Materials and Methods In this prospective pilot study, ICP measurement at the subdural site was achieved with an intravenous cannula and the ventricular site with a ventricular cannula. Both were transduced using a fluid-filled pressure transducer and connected to the monitor for display of the number and the waveforms. Monitoring of intraoperative ICP using both the techniques was done in all patients recruited into the study. The correlation between the two modalities of measurement was studied by the Spearman correlation test and their limits of agreement were studied using the Bland–Altman plot. A case series describing the perioperative management based on the subdural ICP values are also described.Results Subdural ICP showed a strong correlation with intraventricular ICP (rs = 0.93, p = 0.01). Agreement analysis using the Bland–Altman plot showed that the mean difference of ICP between the modalities was 1.44 mm Hg (95% confidence interval, −0.6 to 3.49, p = 0.122).Discussion This study validates the ICP values measured at the subdural site with the intraventricular site. Subdural site ICP monitoring can be achieved rapidly with readily available systems and helps in making intraoperative clinical decisions.Conclusion Cannula-based subdural ICP is a satisfactory alternative to intraventricular ICP monitoring in the intraoperative period.
Keywords: intraoperative intracranial pressure monitoring; intraventricular catheter; subdural catheter; perioperative management